Review of Marina Rojavin, Tim Harte (eds): Soviet Films of the 1970s and Early 1980s: Conformity and Non-Conformity Amidst Stagnation Decay - Bogdan Popa (Apparatus. Film, Media and Digital Cultures of Central and Eastern Europe, 2022)
Review of Soviet Films of the 1970s and Early 1980s: Conformity and Non-Conformity Amidst Stagnation Decay edited by Marina Rojavin and Tim Harte.